2013
DOI: 10.3109/14756366.2013.823957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of novel human cathepsin S inhibitors on cell migration in human cancer cells

Abstract: Elevated cathepsin S (Cat S) level is correlated with higher migration ability in tumor cells. This study investigates the inhibitory effect of novel synthetic a-ketoamide compounds on cathepsin activity and cancer cell migration. The effect of several a-ketoamide compounds on the activity of recombinant cathepsins (Cat S, Cat L and Cat K) was examined. Two highly metastatic cancer cell lines were incubated with three Cat S-specific compounds (6n, 6w and 6r) to analyze their effect on cellular Cat S activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Based on the successfully established radiosynthesis of [ 11 C] 2 , its radiopharmacological investigation in nude mice bearing tumour xenografts derived from MDA‐MB‐231 STn‐Luc cells using PET imaging was enabled. The expression of the oncologically relevant cysteine cathepsins B, L, and S in this aggressive triple‐negative human breast cancer cell line was confirmed by several studies . The PET images are shown in Figures A and A.…”
Section: Resultssupporting
confidence: 57%
“…Based on the successfully established radiosynthesis of [ 11 C] 2 , its radiopharmacological investigation in nude mice bearing tumour xenografts derived from MDA‐MB‐231 STn‐Luc cells using PET imaging was enabled. The expression of the oncologically relevant cysteine cathepsins B, L, and S in this aggressive triple‐negative human breast cancer cell line was confirmed by several studies . The PET images are shown in Figures A and A.…”
Section: Resultssupporting
confidence: 57%
“…The intercellular release of cathepsins into the extracellular space is of oncogenic character, which has been associated with tumor progression and metastasis in various cancer types. As such, cathepsin inhibitors, including the inhibitors of cathepsins D, B, K, E, S, and L, have been developed for cancer therapy. Although many studies have indicated that cathepsins would be effective targets for cancer drugs, there are currently no cathepsin inhibitors that have advanced to clinical trials in cancer.…”
Section: Drugs Targeting the Lysosome In Cancermentioning
confidence: 99%
“…Selective inhibition of cathepsin B leads to limited breast to bone metastasis and reduced invasion of breast cancer cells . Moreover, the inhibition of cathepsin S was reported to reduce the migration of aggressive lung adenocarcinoma and melanoma cells .…”
Section: Proteinases: Structure Functions and Targeting In Cancermentioning
confidence: 99%